2014
DOI: 10.1038/npjpcrm.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of asthma exacerbations with the human-powered nebuliser: a randomised parallel-group clinical trial

Abstract: Background:Nebulisers aid the treatment of respiratory diseases, including asthma, but they require electricity and are often cost-prohibitive for low- and middle-income countries.Aims:The aim of this study was to compare a low-cost, human-powered nebuliser compressor with an electric nebuliser compressor for the treatment of mild to moderate asthma exacerbations in adults and children.Methods:This was a non-blinded, parallel-group, equivalence study, with 110 subjects between 6 and 65 years of age, conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The purpose of this study was to compare the performance of the HPN to an electric nebulizer compressor on key performance measures: volume delivery, pressure and flow characteristics, and delivered particle size distribution. The present study complements two published clinical trials that have demonstrated equivalence between the HPN and an electric nebulizer for the production of sputum samples for TB diagnosis [ 22 ] and for the treatment of patients with mild to moderate asthma exacerbations [ 23 ].…”
Section: Introductionmentioning
confidence: 55%
“…The purpose of this study was to compare the performance of the HPN to an electric nebulizer compressor on key performance measures: volume delivery, pressure and flow characteristics, and delivered particle size distribution. The present study complements two published clinical trials that have demonstrated equivalence between the HPN and an electric nebulizer for the production of sputum samples for TB diagnosis [ 22 ] and for the treatment of patients with mild to moderate asthma exacerbations [ 23 ].…”
Section: Introductionmentioning
confidence: 55%
“…I was intrigued by the recent article by Hallberg et al . 1 on a human-powered nebuliser as such equipment has been used throughout the world for many years. In 1981 Shann 2 described giving asthma treatment by a foot pump-driven nebuliser in Papua New Guinea.…”
mentioning
confidence: 99%